1979
DOI: 10.1159/000181679
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Renal Cortical Interstitium on the Serum Creatinine Concentration and Serum Creatinine Clearance in Different Chronic Sclerosing Interstitial Nephritides

Abstract: 54 biopsy cylinders of patients with different chronic sclerosing interstitial nephritides were investigated morphometrically. The point-counting method was used to determine the relative interstitial volume of the renal cortex. In this study, as in earlier investigations on inflammatory and noninflammatory glomerular diseases, as well as in studies on benign nephrosclerosis, significant positive correlations could be found between serum creatinine concentration and enlargement of the interstitium induced by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…The animals had free access to food and water. At the end of the study period, the animals were housed separately in metabolic cages for 24 h, during which time food and water intake was monitored and 24-h urine output was collected. Total urinary protein excretion was assayed by the sulfosalicyclic acid method in each animal.…”
Section: Methodsmentioning
confidence: 99%
“…The animals had free access to food and water. At the end of the study period, the animals were housed separately in metabolic cages for 24 h, during which time food and water intake was monitored and 24-h urine output was collected. Total urinary protein excretion was assayed by the sulfosalicyclic acid method in each animal.…”
Section: Methodsmentioning
confidence: 99%
“…It is recognized that tubulointerstitial rather than glomerular scarring is the more representative lesion in patients with progressive renal disease [1][2][3]. Although the pathogenesis of interstitial fibrosis has been studied extensively, many unsolved questions remain about the initial cause of fibrosis, the stimuli responsible for its perpetuation and the identity of profibrogenic cells [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Three groups of investigators in London [1], Seattle [2, 3]and Tübingen [4, 5]have shown that in glomerular diseases the impairment of the glomerular filtration rate correlated better with the extent of tubulointerstitial damage than with the degree of the glomerular damage and suggested that the major events which determine the outcome of these diseases probably occur in the interstitium. In these last 15 years, the importance of tubulointerstitial involvement for the progression of renal damage in glomerular diseases has been supported by a continuously increasing amount of clinical and experimental data, emerging mainly from two types of studies: (1) studies of natural history of large cohorts of patients, showing correlations between single clinical or histological features and progression, and (2) studies based on molecular biology and immunohistochemistry of biopsy specimens, showing the expression of the mRNA and/or the protein of single cytokines or growth factors in the epithelial tubular cells, in the leukocytes infiltrating the interstitium and in the resident interstitial fibroblasts.…”
Section: Introductionmentioning
confidence: 99%